Parental phubbing and mobile phone addiction among Chinese adolescents: a moderated mediation model - Ma, Shutao; Bi, Xiaoyan; Cui, Hongbo; Ma, Yankun (Frontiers in Psychology, 2024)
It has been reported that parental phubbing is a significant predictor of mobile phone addiction (MPA) among adolescents. However, the mechanisms underlying this association remain largely unclarified. On the basis of the social learning theories and ecological systems, this study assessed the mediating effect of deviant peer affiliation and the moderating effect of sensation seeking in the association between parental phubbing and MPA among Chinese adolescents. A total of 786 Chinese adolescents (mean age=13.17 years, SD=1.35) completed the questionnaires anonymously about parental phubbing, MPA, deviant peer affiliation and sensation seeking. After controlling for study variables, deviant peer affiliation could partially mediate the association between parental phubbing and MPA among adolescents and this indirect path could be moderated by sensation seeking. Notably, the effect of deviant peer affiliation on MPA was more pronounced in adolescents with higher sensation seeking than in those with lower sensation seeking.